Critical role of iron in the pathogenesis of the murine gangliosidoses - Mylvaganam Jeyakumar (Neurobiology of Disease, 2009)
Neurodegeneration is a prominent feature of the gangliosidoses, a group of lysosomal storage diseases. Here we show altered iron homeostasis in mouse models of both GM1 and GM2 gangliosidoses, which are characterized by progressive depletion of iron in brain tissue. This finding contrasts with the findings in many other neurological disorders, where excess iron deposition has been reported.We found that key regulators of iron homeostasis, hepcidin and IL-6, were increased in gangliosidoses mice. In the brain, the principal iron transport and delivery protein transferrin was reduced, accompanied by a progressive inability of the brain to acquire iron from the circulation. Expression of the transferrin receptor was up-regulated reciprocally. Despite the deregulation of iron homeostasis administration of iron prolonged survival in the diseased mice by up to 38%, with onset of disease delayed and motor function preserved.